1988
DOI: 10.1111/j.1471-4159.1988.tb04854.x
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐Ribosylation of Highly Purified Rat Brain Mitochondria

Abstract: Highly purified synaptic and nonsynaptic mitochondria were prepared from rat brain, and their ADP-ribosyl transferase and NAD glycohydrolase activities were investigated. Data show that there is no significant difference in ADP-ribosyl transferase activity between these two types of subcellular preparations. However, NAD glycohydrolase activity appeared to be much higher in nonsynaptic mitochondria. The specific activity of both enzymes was investigated in the presence of the inhibitor nicotinamide or its anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Although PARP1 activation and the associated cell death response were initially attributed to events in the nuclear compartment, subsequent studies demonstrated the mitochondrial presence of PARP1 and an independent role for mitochondrial PARP1 in mediating cell death. (Masmoudi et al, 1988;Du et al, 2003;Rossi et al, 2009). Based on the results of the PLA assays, we conclude that the mitochondrial PARP1 activation is an early event in oxidant-induced cell injury and, in line with the extranuclear/mitochondrial localization of PKA (Gancedo, 2013;Taylor et al, 2013;Valsecchi et al, 2013), the PKA/PARP1 interactions primarily occur in the extranuclear/mitochondrial compartment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although PARP1 activation and the associated cell death response were initially attributed to events in the nuclear compartment, subsequent studies demonstrated the mitochondrial presence of PARP1 and an independent role for mitochondrial PARP1 in mediating cell death. (Masmoudi et al, 1988;Du et al, 2003;Rossi et al, 2009). Based on the results of the PLA assays, we conclude that the mitochondrial PARP1 activation is an early event in oxidant-induced cell injury and, in line with the extranuclear/mitochondrial localization of PKA (Gancedo, 2013;Taylor et al, 2013;Valsecchi et al, 2013), the PKA/PARP1 interactions primarily occur in the extranuclear/mitochondrial compartment.…”
Section: Discussionmentioning
confidence: 85%
“…Its pathophysiologic overactivation, as a result of oxidative DNA injury, has been implicated in the pathogenesis of several diseases, including neuroinjury, inflammation, and ischemia/reperfusion, and various forms of critical illness (Tulin et al, 2003;Jagtap and Szabo, 2005;DeVos et al, 2012;Szanto et al, 2012;Curtin and Szabo, 2013;Burkle and Virag, 2013). In addition to the nuclear isoform of PARP1 several sets of studies have identified PARP1 in the mitochondrial compartment as well; it appears that, in addition to nuclear PARP1, mitochondrial PARP1 also plays roles in the regulation of various cellular functions-at least in some cell types (Masmoudi et al, 1988;Du et al, 2003;Rossi et al, 2009, reviewed in Burkle andVirag, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increasing evidence indicates that mitochondrial DNA, which is constantly exposed to oxidative damage, is efficiently repaired through at least a subset of the mechanisms involved in nuclear DNA repair (14). A number of previous works reported the occurrence of intramitochondrial poly(ADP-ribosyl)ation (15)(16)(17)(18). Moreover, it has been recently established that PARP-1 hyperactivation can cause the release of apoptosis-inducing factor (AIF) from mitochondria, triggering a caspase-independent cell death pathway (19).…”
mentioning
confidence: 99%
“…However, the capacity for PARP-1 activation within the nucleus to deplete total cellular energy stores, particularly compartmentalized within mitochondria, remains to be established (4,6). Because in addition to being abundant in cell nuclei, PARP-1 and other ADP-ribosyltransferases are also prevalent in mitochondria (7)(8)(9), where similar to nuclear PARP-1, they facilitate DNA repair in response to oxidative damage (10,11), we hypothesized that inhibition of mitochondrial poly(ADP-ribosylation) may play a pivotal role in neuronal cell survival under conditions of oxidative stress and excitotoxicity.…”
mentioning
confidence: 99%